2015
DOI: 10.1158/0008-5472.can-14-0938
|View full text |Cite
|
Sign up to set email alerts
|

miR340 Suppresses the Stem-like Cell Function of Glioma-Initiating Cells by Targeting Tissue Plasminogen Activator

Abstract: Glioma-initiating cells (GIC) have stem-like cell properties thought to be sufficient for recurrence, progression, and drug resistance in glioblastomas. In the present study, we defined miRNA (miR)-340 as a differentially expressed miRNA in human GICs that inhibit GIC-mediated tumorigenesis. Furthermore, we defined tissue plasminogen activator (PLAT) as a critical direct target of miR340 for inhibition. Among miRNAs screened, we found that miR340 expression was decreased in all human GICs and in human glioblas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 38 publications
1
46
0
Order By: Relevance
“…Examination of the expression status, biological function and underlying mechanisms of specific miRNAs in gastric cancer can contribute to the identification of novel biomarkers and therapeutic targets in human gastric cancer. Previous studies have shown that miR-340 plays an important role in human cancers (8)(9)(10)(11)(12)(13)(14). It was found to inhibit the metastatic behavior of breast cancer cells (14) while it decreased the proliferation and promoted the cell apoptosis of prostate cancer cells (13,18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Examination of the expression status, biological function and underlying mechanisms of specific miRNAs in gastric cancer can contribute to the identification of novel biomarkers and therapeutic targets in human gastric cancer. Previous studies have shown that miR-340 plays an important role in human cancers (8)(9)(10)(11)(12)(13)(14). It was found to inhibit the metastatic behavior of breast cancer cells (14) while it decreased the proliferation and promoted the cell apoptosis of prostate cancer cells (13,18).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA-340 (miR-340) has been found to play a critical role in human cancers, including breast (8,9), prostate (10,11), and esophageal cancer (12), hepatocellular carcinoma (13) and glioma (14). Functionally, miR-340 was found to inhibit the migration and invasion of breast cancer cells by inhibiting the Wnt pathway (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mouse primary NSCs, NSCL61 cells, human NSCs (hNSCs, Invitrogen), and GICs (hGICs, E2, E3 and E6) were cultured in DMEM/F12 (Gibco, BRL) supplemented with bFGF (10 ng/mL) and EGF (10 ng/mL; NSC medium), as described previously (8)(9)(10)(11)16). For immunostaining, cells were cultured in chamber slides (Nunc) precoated with fibronectin and poly-D-lysine, as described previously (16).…”
Section: Cell Culturementioning
confidence: 99%
“…Using DNA microarray analysis, we compared the gene expression profiles of mGICs with those of their parental cells and identified genes that increased and decreased in mGICs. By evaluating the candidate genes using human GICs (hGICs) and GBM tissues, we have successfully selected potential GIC-specific genes (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%